PENGUKURAN USABILITY APLIKASI CANVA MENGGUNAKAN SUS (SYSTEM USABILITY SCALE) DAN PENGUJIAN BLACKBOX - Yosua Alexandro; Jadiaman Parhusip (Universitas Widyatama, 2025)
This study aims to assess the usability level of the Canva application using the System Usability Scale (SUS) method and to evaluate the reliability of its core functionalities through black-box testing. As a widely used web-based graphic design platform catering to students, educators, and creative professionals, Canva requires a high level of usability to ensure that users can work efficiently and comfortably. This research employed a descriptive quantitative approach and involved 30 active Canva users as respondents. The research instruments consisted of a SUS questionnaire containing ten statements that measure user perceptions of ease of use, efficiency, and comfort, as well as a black-box testing checklist designed to verify whether Canva’s main features functioned according to the expected system behavior. The SUS results indicate an average score of 72.42, categorized as “Good,” signifying that Canva is generally easy to use and acceptable to the majority of users. Meanwhile, the black-box testing, which comprised 16 test scenarios across essential Canva features, achieved a success rate of 93.75%, with one failure involving a slight delay in the drag-and-drop feature. The integration of both analyses reveals that the positive user perceptions are supported by stable and reliable system performance. This study thus provides a comprehensive overview of Canva’s user experience quality and feature reliability, offering valuable insights for developers and researchers conducting further evaluations on web-based design applications.